The emperor has no clothes: a synthesis of findings from the Transformative Research on the Alcohol industry, Policy and Science research programme. - McCambridge, Jim; Mitchell, Gemma; Lesch, Matthew; Filippou, Andreas; Golder, Su; Garry, Jack; Bartlett, Andrew; Madden, Mary (Addiction, 2023)
Background and Aims: The Transformative Research on the Alcohol industry, Policy and Science (TRAPS) programme investigates the alcohol industry, with an innovative focus on public health sciences. TRAPS adds to an under‐developed literature on the study of alcohol industry influence on alcohol science and policymaking. This paper provides a synthesis of TRAPS findings to inform future research. Methods: We conducted an interpretive review of TRAPS research findings across its component studies, identifying and integrating the key contributions made by individual studies to the literature on alcohol policymaking and science, and identifying areas where TRAPS progress was limited. This produced themes for consideration in future research agenda setting. Results: TRAPS explored the interventions of the alcohol industry in science and policymaking using various methods, including systematic reviews and qualitative interviews. These studies identified the industry's activities in several key areas, such as the debate over minimum unit pricing (MUP), cardiovascular health and alcohol research and a long‐running public relations programme developed in close connection with the tobacco industry. Collectively, the research shows that alcohol policymaking has involved a contest between the research community and alcohol industry actors about whether and how science should be used to inform policy. Conclusions: The TRAPS programme demonstrates the need for a transdisciplinary approach to understand the nature of corporate political activity; the crucial role industry involvement in science plays in the development of corporate political power; and how public health actors have successfully overcome industry opposition to evidence‐based policies. Advances in alcohol policy should be underpinned by strong, reflexive public health sciences, alert to the role of industry in the alcohol harms under study and thorough in their investigation of the alcohol industry as an object of study in itself.